THE INFLUENCE OF SINBIOTIC YOGURT ON MICROSCOPICAL FREQUENT USING MICROSCOPES ON THE WISTAR RATS (Rattus norvegicus) - Janggu, Jayanthi Petronela (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Escherichia coli are a gram-negative bacteria belonging to the normal human intestinal flora. Excessive type of E.coli pathogen bacteria could cause infectious disease for humans. In the gastrointestinal tract, especially in the small intestine, the pathogen that often causes interference is Enteropathogenic Escherichia coli. Growth of pathogenic bacteria could be inhibited by administration of sinbiotic yogurt. Synbiotic yogurt is a yogurt that is supplemented with probiotics and prebiotics. Probiotics used were Lactobacillus bulgarius, Streptococcus thermophiles, Bifidobacterium bifidium with the addition of prebiotics i.e. purple sweet potato containing oligosaccharides. The aims of this study was to saw the effect of giving sinbiotic yogurt to microscopic images of the small bowel of wistar rats. This research was a laboratory experimental research. The subjects consisted of 24 wistar rats divided in the control group (6 tails) and the treatment group (18 tails) divided into 3 groups with 6 each group. The results of group I with histologic features of normal intestinal tissue, group II partial epithelial mucosal epithelium seen erosion, group III with epithelial cell surface epithelial mucosa appear normal and group IV with epithelial surface erosion but, cell regeneration was characterized by increasing goblet cells . The administration of sinbiotic yogurt given E. coli had a good effect of improving the epithelial cells of the small intestine surface by increasing goblet cells. Keywords: Escherichia coli, sinbiotic yogurt, small intestinal mucosa.